Preserving Diversity: Lessons from Batang Tarang Village of West Kalimantan - Hermansyah Hermansyah; Faisal Abdullah; Mochamad Hamdan (Al-Albab, 2022)
The recurring communal, racial conflicts in West Kalimantan have left unpleasant memories among the local community. Unfortunately, some people believe that similar events will keep happening. This article was based on field research that relied on interviews and observations involving several crucial things. This research argues that communal conflicts in West Kalimantan can be averted by empowering internal forces to maintain balance in a plural society. This article found that conflict-prone societies such as those in Batang Tarang have the capacity to build harmony through togetherness, inter-ethnic marriages, the moderate practice of Islam, fair practice of adat [customary law], and strengthening awareness of shared origins.